Análisis de la cuenta por cobrar de los usuarios de CNEL Los Ríos en el periodo 2019-2020 - Nuñez Mayorga, Walter Patricio (2021)
The purpose of the Strategic Public Electricity Corporation National Electricity Corporation CNEL EP is to provide the public service of distribution and commercialization of electric energy, within the assigned area, under the exclusive regime regulated by the State, in order to satisfy the demand for energy. electricity, under the conditions established in the regulations applicable to the electricity sector and supply electricity to consumers. This case study is called "Analysis of accounts receivable from CNEL Los Ríos users in the 2019 and 2020 period, an investigation was carried out in order to reveal the percentage variation of the accounts. The electricity company has had changes Due to the pandemic, users have increased in the claims of the payroll due to excessive consumption. In order to achieve the proposed objective, the inductive research method was applied, which revealed the problems that arose when carrying out the billing process. , the approach determined was quantitative, by means of which an analysis of the results was carried out using statistical tables and graphs, allowing to know the veracity of the percentage variations of accounts receivable and to verify the increase or decrease of the year 2019 and 2020.